Heightened splenic and bone marrow uptake of 18F-FDG PET/CT is associated with systemic inflammation and subclinical atherosclerosis by CCTA in psoriasis: An observational study. (December 2021) - Patel, Nidhi H.; Osborne, Michael T.; Teague, Heather; Parel, Philip; Svirydava, Mariya; Sorokin, Alexander V.; Teklu, Meron; Manyak, Grigory; Zhou, Wunan; Pantoja, Carla; Scott, Colin; Playford, Martin P.; et al.
Abstract: Background and aims: Psoriasis is an immune-mediated inflammatory disease with increased risk of myocardial infarction. Preclinical studies in psoriasis models show an association between chronic inflammation and immune cell proliferation in the spleen and bone marrow (BM). We sought to test the hypothesis that splenic and BM 18 F-fluorodeoxyglucose ( 18 F-FDG) uptake is heightened in psoriasis and that higher uptake associates with systemic inflammation and subclinical atherosclerotic disease measures in this cohort. Methods: Multimodality imaging and biomarker assays were performed in 240 participants (210 with psoriasis and 30 healthy). Splenic and BM uptake was obtained using 18 F-FDG positron emission tomography/computed tomography (PET/CT). Coronary artery plaque characteristics including non-calcified burden (NCB) and lipid rich necrotic core (LRNC) were quantified using a dedicated software for CT angiography. All analyses were performed with StataIC 16 (Stata Corp., College Station, TX, USA). Results: Splenic and BM 18 F-FDG uptake was increased in psoriasis ( vs. healthy volunteers) and significantly associated with proatherogenic lipids, immune cells and systemic inflammation. Higher splenic 18 F-FDG uptake associated with higher total coronary burden (β = 0.37; p< 0.001), NCB (β = 0.39; p< 0.001), and LRNC (β = 0.32; p< 0.001) in fully adjusted models. Similar associations were seen for BM 18 F-FDG uptake in adjusted models (β = 0.38; β = 0.41; β = 0.24; respectively, all p< 0.001). Conclusions: Heightened splenic and BM uptake of 18 F-FDG is associated with proatherogenic lipids, immune cells, inflammatory markers and coronary artery disease. These findings provide insights into atherogenic mechanisms in psoriasis and suggest that immune cell proliferation in the spleen and BM is associated with subclinical atherosclerosis. Graphical abstract: Image 1 Highlights: Splenic and bone marrow (BM) uptake represents heightened immune cell proliferation. Splenic and BM uptake relates to atherogenic lipid, immune and inflammatory measures. Splenic and BM uptake relates to non-calcified burden and lipid rich necrotic core.